PENINGKATAN KEMAMPUAN LITERASI-NUMERASI SISWA DAN UPAYA REVITALISASI SEKOLAH MELALUI PROGRAM KAMPUS MENGAJAR - Dian Bayu Firmansyah; Fiskiyatur Rohmah; Wulan Fabilla (LPPM Universitas Bina Bangsa, 2022)
This community service activity aims to help improved students' basic literacy skills and also help the learning process and technology application at SDN Gebangarum 2, Demak Regency, Central Java. The community service activity take place from August 2, 2021- December 12, 2021. To solve existing problems, the community service team designed and implemented several structured work programs, such as: classroom learning assistance, technology adaptation, assisting school administration and teachers, and building school facilities. From the results of the implementation of the activities that have been carried out, it is known that there is an increase in motivation and the number of student participation in participating in learning in class. The home visit work program carried out by the community service team is also very helpful for teachers and students when the implementation of learning is carried out during a pandemic. Furthermore, the assistance of technology adaptation for learning and school administration has also succeeded in solving several administrative problems and also the use of learning applications that have not previously been implemented. Finally, the construction of additional facilities in the school such as reading corners and hanging gardens, has a positive impact on improving students' basic literacy, and the aesthetics of the school environment. The community service program through the Kampus Mengajar program is very useful for both students, teachers, schools and student implementation teams, especially in relation to problem solving and the implementation of theories and knowledge gained in lectures